2012
DOI: 10.1155/2012/532154
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Barriers to Effectiveness of Interventions to Prevent Mother-to-Child Transmission of HIV in Arba Minch, Ethiopia

Abstract: Objectives. Despite the availability of services to prevent mother-to-child transmission (PMTCT) of HIV, socio-cultural, health system and operational factors constrain many pregnant women from accessing services or returning for followup thereby increasing the risk of vertical transmission of HIV to newborns. We highlight and describe unique contextual factors contributing to low utilization of PMTCT services in Arba-Minch, Ethiopia. Methods. Qualitative research design was utilized to obtain data through foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 27 publications
(43 reference statements)
4
32
0
2
Order By: Relevance
“…This study also revealed that health care related factors such as cost of the drug, not getting friendly service from health facility, and long waiting times were frequently mentioned factors for not continuing PMTCT service utilization. This is in line with findings of other study done in Ethiopia revealed that health workers are not happy to handle deliveries for women who are known HIV positive due to fear of accidental infection [22]. Other studies have also had similar findings [17,23,[28][29][30][31].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study also revealed that health care related factors such as cost of the drug, not getting friendly service from health facility, and long waiting times were frequently mentioned factors for not continuing PMTCT service utilization. This is in line with findings of other study done in Ethiopia revealed that health workers are not happy to handle deliveries for women who are known HIV positive due to fear of accidental infection [22]. Other studies have also had similar findings [17,23,[28][29][30][31].…”
Section: Discussionsupporting
confidence: 90%
“…Frequently mentioned individual and family related factors identified in this study were fear of divorce, lack of family support, lack of partner support and lack of time. Like our research, other studies found that non-disclosure of HIV status, fear of divorce, fear of HIV stigma, and lack of partners support were some of the most common barriers to PMTCT service utilization [16,[19][20][21][22][23][24][25][26]. Another study in Sudan [27], and in Malawi [28] also revealed that women are not likely to disclose their HIV status due to stigma.…”
Section: Discussionsupporting
confidence: 72%
“…8%) were conducted in 2013 (28,35,40) and 3 (15. 8%) were conducted in 2012 (22,33,37). Two studies (10.…”
Section: Resultsmentioning
confidence: 99%
“…HCWs were critical to helping build the motivation and resulting empowerment for women to adhere to the PMTCT program, through effective education regarding the efficacy of PMTCT. Nyasula and others found that shortage of HCWs in Malawi and other settings leads to inadequate PMTCT program education and inaccurate assessments of participants' situations [19] [20]. Ensuring that there are HCWs knowledgeable about and trained to deliver effective education as a core component of antenatal and HIV services will be important to achieving the patient motivation related to a belief in the promise of PMTCT.…”
Section: Discussionmentioning
confidence: 99%